2016
DOI: 10.1111/jocn.13219
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of patient experiences of Type 2 Diabetes care delivered comparatively by General Practice Nurses and Medical Practitioners

Abstract: The findings are relevant to primary health care clinicians providing diabetes care to inform more relevant supportive care by general practice nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…Among the health care professionals involved in DM management and patients care, the role of the nurses is of increasing importance because of the increasing global prevalence of DM 10 . Consequently, nurses are essential in the multidisciplinary team to provide appropriate care to DM patients and to manage DM, both in primary and secondary care settings 11 . Several papers have assessed the knowledge of dental students and dental care providers [12][13][14][15][16] , internists and endocrinologists 3,17,18 , diabetes educators 19 and diabetic patients [20][21][22][23][24] of the association between DM and oral health.…”
Section: Resultsmentioning
confidence: 99%
“…Among the health care professionals involved in DM management and patients care, the role of the nurses is of increasing importance because of the increasing global prevalence of DM 10 . Consequently, nurses are essential in the multidisciplinary team to provide appropriate care to DM patients and to manage DM, both in primary and secondary care settings 11 . Several papers have assessed the knowledge of dental students and dental care providers [12][13][14][15][16] , internists and endocrinologists 3,17,18 , diabetes educators 19 and diabetic patients [20][21][22][23][24] of the association between DM and oral health.…”
Section: Resultsmentioning
confidence: 99%
“…Although most international literature established the positive impact nurses in advanced practice bring to care, role delineation between RNs and advanced practice nurses (APNs) remains unclear (Boyle, Saunders, & Drury, ; Woo, Zhou, Lim, & Tam, ). For instance, Australian health care consumers reported their inability to differentiate nurse practitioners (NPs) from other categories of nurses and were perplexed about the NP role and scope of practice (Parker et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Adopting this perspective leads to considering the evidence of effectiveness to be insufficient for the question at hand. Two qualitative studies7 8 were identified and provided some of the needed details. The studies shed light on the psychological factors that should be addressed when delivering diabetes management programmes and provided insight on the factors that affect adherence to such programmes (table 1).…”
Section: Examplementioning
confidence: 99%
“…For example, studies demonstrated that before providing education in diabetes, we should address negative feelings that individuals have (anger about the initial diagnosis, and subsequently negotiate loss of control of a person's own lifestyle and environment) 7. Qualitative studies also provided explanation to lack of adherence to a programme (individual, organisational and content factors) 8.…”
Section: Examplementioning
confidence: 99%